Visualizing Labour: The Problem and a Case Study, U.S.S.R. in Construction1. Issue 2 (July 2019) - Dell, Simon
Abstract : This essay examines the twofold problem of 'visualizing labour'. A first part of the problem is the status of 'labour' and its relationship with 'work'. A second issue is the status of 'visualization', which, as the process of conceiving images, is distinct from the process of representing given entities. These issues are rather entangled; here they are addressed in the context of Soviet Russia. I argue that from the inception of the first Five-Year Plan in April 1929, there was a need to visualize labour: this was integral to Josef Stalin's project of socialist construction. One result was the presentation of the worker as a very particular kind of hero. Such was the case for Viktor Kalmikov in U.S.S.R. in Construction.